2022
DOI: 10.30604/jika.v7is1.1210
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Murottal Al-Quran on Anxiety Levels Toward IX Class Students in Facing Examination at The Junior High School of Muhammadiyah 1 Kalirejo Central Lampung

Abstract: Anxiety is a psychological reaction in the form of bad feelings that can be experienced by anyone, including students who will undergo the National Examination. The level of anxiety that occurs depends on family support, environment and readiness to face something. Actions that can be taken to reduce anxiety include listening to murottal Al-Quran because listening to the Al-Quran can calm one's soul, so that it can reduce anxiety. The objective of the study was to determine the effect of murottal Al-Quran on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Furthermore, listening to the Murottal Al-Quran can be an alternative therapy for adolescents. Previous research has shown that listening to Murottal Al-Quran can reduce the Anxiety Level of Grade IX Students in Facing Exams at Junior High School Muhammadiyah 1 Kalirejo, Central Lampung [13]. Combining yoga and Murottal Al-Qur'an has been shown to reduce the dysmenorrhea pain scale in adolescents by increasing beta-endorphin levels [14].…”
mentioning
confidence: 99%
“…Furthermore, listening to the Murottal Al-Quran can be an alternative therapy for adolescents. Previous research has shown that listening to Murottal Al-Quran can reduce the Anxiety Level of Grade IX Students in Facing Exams at Junior High School Muhammadiyah 1 Kalirejo, Central Lampung [13]. Combining yoga and Murottal Al-Qur'an has been shown to reduce the dysmenorrhea pain scale in adolescents by increasing beta-endorphin levels [14].…”
mentioning
confidence: 99%